Termite fauna of Marai Parai - Gurkha Hut, Kota Belud, Sabah, Malaysia - Homathevi Rahman; Marcellus Nicholsonn -Sanai@Marcus; Ginik Lunsin (Sabah Parks Nature Journal, 2024)
Termites are essential for soil health, breaking down organic matter and recycling nutrients, which supports plant growth and biodiversity, making their species composition crucial for maintaining the balance and resilience of natural ecosystems. This paper presents a preliminary checklist of termite species collected from Nunuk Subcamp, part of Marai Parai Gurkha Hut area. Termites were manually collected using standardized 100 m x 2 m belt transect. A total of 19 termite species of 13 genera of two families (Rhinotermitidae and Termitidae), were documented within the forest sites of Nunuk Subcamp. The assemblage is dominated by the family Termitidae (90%), the largest and most common family comprising of both soil and wood dwelling termites. Wood feeders dominated the assemblage, making up 48% of the composition, indicating their prevalence in the study area, followed by soil-feeders at 42%, highlighting their significant presence in the local termite community. The termite diversity in this area is notably lower compared to what is typically found in Malaysian primary forests, where all the mentioned termite species are commonly observed.